University Stakeholders' Awareness and Knowledge on the Nature and Forms of Cyberbullying - Villa, Elizabeth B.; Concina, Judith F.; Deypis, Alicezon D.; Peña, Joshua P.; Vida, Pauline Ericka Z.; Golla, Nathaniel S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Cyberbullying has emerged as a pressing issue in the digital age, af-fecting individuals across various demographics and social groups. This study examines university stakeholders' awareness and knowledge regarding the nature and forms of cyberbullying. Employ-ing a descriptive-survey research design, data were collected from students, faculty, non-teaching staff, and administrators through a structured questionnaire. The findings indicate that while there is a high level of awareness about cyberbullying and its consequences, gaps remain in understanding specific forms and preventive measures. The study highlights the crucial role of universities in fos-tering a safer digital environment through policy implementation, awareness campaigns, and support mechanisms. It also emphasizes the need for collaborative efforts among stakeholders to mitigate the risks of cyberbullying. The study recommends the enhancement of institutional policies, increased training sessions for university members, and the integration of digital literacy programs to promote responsible online behavior.